Porous Zeolitic Imidazolate Framework Loaded Mn as an Efficient Catalyst for the Selective Catalytic Reduction of NOx with NH3 - Yongliang Chen; Meiqing Yu; Rui Wang (Aerosol and Air Quality Research)
Abstract Zinc 2-methylimidazolate (Zn(Me-Im)2, ZIF-8) was synthesized through solvothermal method, and the Mn@ZIF-8 was synthesized by loading the Mn species onto the prepared ZIF-8 through impregnation. The effect of the addition amount of Mn species on the activity in selective catalytic reduction of NOx with NH3 (NH3-SCR), the stability of catalysts at ideal temperatures and the resistance to H2O and SO2 were investigated. Moreover, the characterizations of the catalysts including XRD, SEM, EDS, XPS, BET, TGA and H2-TPR were carried out. The results indicated that SCR activity of the catalysts was related to the addition amount of Mn species, the Mn@ZIF-8(0.8) showed the best NO conversion of over 90% ranging from 225°C–400°C with good stability in a long-time test. Besides, the Mn@ZIF-8 showed a high resistance to SO2. The ZIF-8 has a great potential to be an excellent support, and Mn@ZIF-8 is promising catalyst in SCR reaction.